METHOD OF CASE MODELING - P. N. Vishnevskiy (Высшее образование в России)
The article presents the method of case modeling used in the process of education within the programs of higher humanitarian education. The author dwells on the problems of current learning methods, as well as on the existing methods of their solution. The paper reviews the flaws of the current methods from the standpoint of “soft” and “hard” skills, which are necessary for graduates. Following the analysis the author suggests using the method of case modeling which is applicable within the modern programs of higher humanitarian education. One of the characteristics of case modeling method is staging: details and facts are appended step-by-step to the general description of a problem. In conclusion the author compares the presented method of modeling of problem situations with the other educational methods, such as lecture, self-dependent research.